Astroturfing Global Warming: It Isn’t Always Greener on the Other Side of the Fence - Cho, Charles H.; Martens, Martin L.; Kim, Hakkyun; Rodrigue, Michelle (2011)
Astroturf organizations are fake grassroots organizations usually sponsored by large corporations to support any arguments or claims in their favor, or to challenge and deny those against them. They constitute the corporate version of grassroots social movements. Serious ethical and societal concerns underline this astroturfing practice, especially if corporations are successful in influencing public opinion by undertaking a social movement approach. This study is motivated by this particular issue and examines the effectiveness of astroturf organizations in the global warming context, wherein large corporate polluters have an incentive to set up astroturf organizations to undermine the importance of human activities in climate change. We conduct an experiment to determine whether astroturf organizations have an impact on the level of user certainty about the causes of global warming. Results show that people who used astroturf websites became more uncertain about the causes of global warming and humans’ role in the phenomenon than people who used grassroots websites. Astroturf organizations are hence successful in promoting business interests over environmental protection. In addition to the multiple business ethics issues it raises, astroturfing poses a significant threat to the legitimacy of the grassroots movement.
Keywords: Rhetoric; Legitimacy; Grassroots organizations; Global warming; Climate Change; Business Ethics; Astroturfing